Seasonal occurrence of Oithona similis (cyclopoida), Microsetella norvegica (harpacticoida) and Microcalanus spp. (calanoida), and productivity of O. similis, in three high-latitude Norwegian fjords. - Glad, Peter (UiT Norges arktiske universitet, 2018)
The Seasonal population dynamics of the small copepod species Oithona similis (cyclopoida), Microsotella norvegica (harpacticoida) and Microcalanus spp. were investigated in the northern Norwegian fjords Balsfjord, Altafjord and Porsangerfjord. In this study a WP-2 net with 64 µm mesh size was used to sample all the stages of O. similis, M. norvegica and Microcalanus spp. Copepodite stages CI – CVI were identified for each species to determine seasonal distribution population structure. To assess the relative importance of small copepod species in the marine ecosystem, the seasonal and annual secondary production of O. similis in the three study fjords was estimated. Production was estimated with specific egg production rates, that is based on experimentally determined egg hatching rates, and a temperature-dependent method. The species were present year-round in the fjords but differed from each other in both geographical and seasonal distribution, but all copepodite stages for each specie was present in all sample months. In December, copepod abundance and biomass were low with the exception of inner Porsangerfjord and Balsfjord. In March, peak in total copepod abundance and biomass was observed in inner Porsangerfjord and Balsfjord while in the other areas this remained low. In April, March and October, abundance and biomass were comparatively less than the peak found in March. Population abundance for O. similis remained relatively stable during the months and seasons, where all life stages were observed during the study that indicated year-round reproduction. M. norvegica accounted for the high abundance found in December and March at inner Porsangerfjord and Balsfjord, that mainly consisted of overwintering stages (females without eggs and CIV – CV copepodites). Egg carrying M. norvegica females was first observed in small numbers in April and in greater numbers in August. All stages of Microcalanus spp. was found during this study but was less abundant than the other two species. Reproduction for ...